VD_FINDINFO Arrêt / 2021 / 479 vom 9. Juli 2021 - VD Tribunal cantonal (2021)
DEGRÉ DE L'INVALIDITÉ, ÉVALUATION DE L'INVALIDITÉ, MEMBRE D'UNE COMMUNAUTÉ RELIGIEUSE | 28a al. 2 LAI, 4 LAI, 8 al. 3 LPGA, 27 RAI